A Survey of Current Procurement Travel Practices, Accident Frequency, and Perceptions of Safety. Issue 10 (October 2019) - Schenk, Austin D.; Washburn, William K.; Adams, Andrew B.; Lynch, Raymond J.
Abstract : Background: In 2018, 81% of the 36, 529 solid organs transplanted in the United States came from deceased donors. These organs were recovered through widespread use of aeromedical and emergency ground transportation systems. Urgently scheduled travel to remote hospitals at night and in varied weather conditions carries risk for the transplant professionals involved. A landmark survey conducted in 2007 demonstrated that 80% of respondents had experienced a "near-miss" event while on a procurement trip, and 15% had been involved in at least 1 accident. One decade later, we sought to revisit the issue of procurement related travel safety. Methods: A 32 question survey designed to interrogate travel practice, accident frequency, and perceptions of safety was sent to the American Society of Transplant Surgeons membership. Results: Our survey response rate was 20.6%. At least 1 travel accident with bodily injury was reported by 23% of respondents and yet only 7% of respondents reported feeling "unsafe" or "very unsafe" during procurement travel. Sixteen percent of respondents participated in a procurement at a dedicated organ procurement facility, and only 53% of procurement surgeons completed at least 1 deceased donor procurement at their own hospital facility within the preceding 12 months. Conclusions: In a field where increasingly aggressive organ utilization is the norm, the efficiency and safety of procurement travel merits ongoing consideration. Addressing these concerns takes on new significance as organ allocation policies change geographic distribution to expand the extent of travel required for surgical teams. Abstract : Supplemental Digital Content is available in the text.